2012
DOI: 10.1186/1465-9921-13-13
|View full text |Cite
|
Sign up to set email alerts
|

"GOLD or lower limit of normal definition? a comparison with expert-based diagnosis of chronic obstructive pulmonary disease in a prospective cohort-study"

Abstract: BackgroundThe Global initiative for chronic Obstructive Lung Disease (GOLD) defines COPD as a fixed post-bronchodilator ratio of forced expiratory volume in 1 second and forced vital capacity (FEV1/FVC) below 0.7. Age-dependent cut-off values below the lower fifth percentile (LLN) of this ratio derived from the general population have been proposed as an alternative. We wanted to assess the diagnostic accuracy and prognostic capability of the GOLD and LLN definition when compared to an expert-based diagnosis.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
104
1
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(132 citation statements)
references
References 33 publications
3
104
1
9
Order By: Relevance
“…We also used both the LLN and the GOLD defi nitions of AFO, achieving similar results for both despite the limitations of each method. 18 Regardless of the AFO criteria used, we found that as BMI increased, so did the likelihood of COPD misdiagnosis.…”
Section: Limitationsmentioning
confidence: 83%
See 1 more Smart Citation
“…We also used both the LLN and the GOLD defi nitions of AFO, achieving similar results for both despite the limitations of each method. 18 Regardless of the AFO criteria used, we found that as BMI increased, so did the likelihood of COPD misdiagnosis.…”
Section: Limitationsmentioning
confidence: 83%
“…These findings have important implications because obese patients are at greater risk of diabetes, hypertension, coronary heart disease, and mortality compared with normal weight patients. [17][18][19] Among obese patients misdiagnosed with COPD, missing the chance to diagnose and treat other conditions associated with dyspnea, particularly cardiovascular disease, may put them at even greater risk of poor health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although GP-reported COPD diagnosis is not the gold standard, it is the real-life situation. In another study, even when using diagnosis by a panel of lung disease experts, 17% of cases were missed by the fixed and 28% by the LLN cut-off, while airflow limitation by the fixed cut-off had higher agreement with the expert panel's diagnosis [23].…”
Section: Discussionmentioning
confidence: 99%
“…It is simple and independent of reference values and has been used in numerous clinical trials. This criterion may lead an over-and underestimation of airflow obstruction depending on age compared with the lower limit of normal (LLN) values [22,23]. In concordance with GOLD, the TTS has encouraged clinicians to perform spirometry.…”
Section: Diagnosismentioning
confidence: 99%